If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 22 = 3 Reorder the terms: 22 + 12x = 3 Solving 22 + 12x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-22' to each side of the equation. 22 + -22 + 12x = 3 + -22 Combine like terms: 22 + -22 = 0 0 + 12x = 3 + -22 12x = 3 + -22 Combine like terms: 3 + -22 = -19 12x = -19 Divide each side by '12'. x = -1.583333333 Simplifying x = -1.583333333
| 9-5-3=1 | | 9-5-1=1 | | 25x^3-25p^2-x+1=0 | | 12x-x^2-32=0 | | -6c^2+4x=68 | | c^3+4c^2-9x-36=0 | | 0=-8x^2+7x+4 | | 14x+27=70 | | 4=0.6z | | 10w+6=w-15 | | 8p+5(-8p-5)=167 | | 0=-6x^2+3x+5 | | -0.8(0.3x+0.4)=11.3 | | 8p+5(-8-5)=167 | | 4p-2=0.25p+10 | | 5x^2+90x+2005=0 | | 4y=8y-8 | | 3v+-9=7+2v-v | | 17b-11d+4c= | | 186+x=4 | | 4-6+9-6=1 | | 4=2*3z | | 3r-9=7+2v-v | | 9x^4-42x^2+49=0 | | 11u-35-130=12u-17 | | z+82=43z-44 | | -2x^6-16=0 | | 1/4-5/14= | | (2u)(2u^3y^6)(8y^7)= | | 9x^2+163x+654= | | -1.7x=-0.2x-0.6 | | 10x^2+11xy-6y^2=0 |